The Worst Earthquakes on Record - Troup, Roxanne (Mitchell Lane Publishers Inc., 2025)
Earthquakes are among the world$1 (Bs deadliest natural disasters. This ground shaking can have different causes, including natural processes that occur within the earth and certain human activities. Earthquakes can be devastating on their own, killing many people when they strike. But they can also trigger other types of natural disasters, such as fires, landslides, and tsunamis. Part of The Earth$1 (Bs Worst Natural Disasters series, The Worst Earthquakes on Record discusses some of the strongest and deadliest earthquakes in history. It also explains how these devastating natural disasters happen and what people can do to protect themselves if they ever experience one.s